Proposta de uma metodologia de projetos aplicada no detalhamento de estruturas metálicas - Conto, Lucas De (2021)
With the growth of civil construction, there was an increase in the demand for renowned professionals to develop, with agility and efficiency, the detailing projects in the various metallic undertakings. The objective of this work is to present a methodology applied in the detailing of metallic structures. The work method consists of an exploratory research with professionals in the field of projects, guaranteeing access to qualitative and technical information through an unstructured interview related to professional practice. It was applied in a steel structure company, where the project stages were developed: basic project, executive project, anchoring project, detailing project and assembly project. Among the main conclusions, the work aims to contribute to the activity of new professionals and especially in the process of detailing metallic structures, in order to optimize the product development phases.